Cover Image, Volume 60, Issue 11. Issue 11 (14th October 2021) - Kato, Akihisa; Ng, Serina; Thangasamy, Amalraj; Han, Haiyong; Zhou, Wendi; Raeppel, Stephane; Fallon, Michael; Guha, Sushovan; Ammanamanchi, Sudhakar
Abstract : The cover image is based on the Research Article A potential signaling axis between RON kinase receptor and hypoxia‐inducible factor‐1 alpha in pancreatic cancer by Akihisa Kato et al., https://doi.org/10.1002/mc.23339 .